Talitrid amphipods from ocean beaches along the New South Wales coast of Australia (Amphipoda, Talitridae) - Lowry, J. K. (Zootaxa, 2012)
The sand-hopper Bellorchestia mariae sp. nov. is described from Honeymoon Bay on the north coast of Jervis Bay, NewSouth Wales, Australia. It is the sister species of B. richardsoni Serejo & Lowry, 2008 and appears to have a limited dis-tribution from about Narrawallee in the south to northern Jervis Bay. The distribution of B. richardsoni Serejo & Lowry,2008 is extended from Point Ricardo, Victoria, northwards to Ulladulla on the New South Wales coast. A new synonymyis proposed for the sand-hopper Notorchestia quadrimana (Dana, 1852) which includes N. novaehollandiae (1899) andN. lobata Serejo & Lowry, 2008. It is considered to be a wide-ranging species from Shark Bay in Western Australia aroundthe south coast to at least Maitland Bay in central New South Wales. The beach-hopper Orchestia dispar Dana, 1852 isdescribed from Valla Beach in northern New South Wales and moved to the new genus Vallorchestia. This is the first re-cord of V. dispar since its original description 160 years ago. The beach-hopper Platorchestia smithi sp. nov. is describedfrom Brooms Head, New South Wales, Australia. It is common on ocean beaches from Bendalong in the south to Ballina in northern New South Wales. South of Bendalong beach-hoppers on ocean beaches appear to be absent.